-10+3k=k-3k

Simple and best practice solution for -10+3k=k-3k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10+3k=k-3k equation:


Simplifying
-10 + 3k = k + -3k

Combine like terms: k + -3k = -2k
-10 + 3k = -2k

Solving
-10 + 3k = -2k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '2k' to each side of the equation.
-10 + 3k + 2k = -2k + 2k

Combine like terms: 3k + 2k = 5k
-10 + 5k = -2k + 2k

Combine like terms: -2k + 2k = 0
-10 + 5k = 0

Add '10' to each side of the equation.
-10 + 10 + 5k = 0 + 10

Combine like terms: -10 + 10 = 0
0 + 5k = 0 + 10
5k = 0 + 10

Combine like terms: 0 + 10 = 10
5k = 10

Divide each side by '5'.
k = 2

Simplifying
k = 2

See similar equations:

| g^2=25/4 | | -123+2x-9x=38 | | 5x^2-7x-6=y | | 6a-7+2= | | 5(1-5m)=155 | | -85-3x-7x=65 | | -1x^2-11x+26=0 | | 4(3-2x)+6(x-3)=7x-5 | | 2a^2b/4ab^2 | | 3x+5x-92=28 | | x^2-3x+16x=0 | | d^2=9 | | y-7=5x-5 | | 5x^4+10x^3=0 | | 8(n-4)=-88 | | 11x-9x-12=16 | | 15+4x-8=14x-2-7x | | 2b-1-2=11 | | 4x-79+3x=68 | | -3(5P+6)-2(5-11P)=3(8+2P) | | 1/49^2 | | 15x-8whenx=4 | | 4x+24=2x-36 | | M^2+8m+13=0 | | -8k-4k=0 | | -x+6x-82=43 | | (2x-16)=(x+16) | | 9x-4+2x-6=5x-2+3x+5 | | 1/25^2 | | 116+5x-28+64+3x=360 | | x^4-8x^3+16x^2+8x-16=0 | | (7Y+5)-(3+6Y)=12 |

Equations solver categories